Desain Sistem Kontrol Ruang Pertumbuhan Ulat Sutera untuk Meningkatkan Kualitas Produksi Sutera Alam - Lilik Sutiarso; Atris Suyantohadi; Hari Purwanto (agriTECH, 2004)
The world demand of raw-silk provides a great opportunity to the development of raw-silk production in Yogyakarta. Recently, only 21% out of the overall world demand of raw-silk is fulfilled, whereas Indonesia contributes only 0.1% per year. The main problem is the lack of quality of raw-silk. The optimum growth of silkworm depends on micro environments, i. e. temperature, humidity, aeration, and light intensity. The research was aimed, to apply an automated -"on/or control technology in the silkworm rearing environmental monitoring. The result expected is high-grade quality of cocoon. In the research, two different conditions of silkworm growing environments were compared: controlled environment (in the rearing box) and normal environment. Then, from third instar (silkworm's growth stage) to cocoon's stage (final stage or fifth instar), temperature and air humidly were set on 24Â°C - 26Â°C and 70% - 80% 'respectively. While, Aeration and light intensity were ranged 0.1 - 0.3 m/s and 15 - 30 lux for all instar stages (constant) respectively. The result indicated that there was an increasing the percentage of cocoon skin's grade in the controlled rearing environment (19.66%), compared to the result of normal rearing environment (18.56%), also there was significantly different result on the thickness of the cocoon produced